Seroprevalence and factors associated with Chlamydia trachomatis infection among subfertile couples attending local public subfertility clinic - Nekmat, Nily Waheeda (2020)
Chlamydia trachomatis is one of the agents that cause the sexually transmitted infections called chlamydia. People practicing risky sexual behaviours such as having multiple sex partners, exercising sexual intercourse at an early age, and undergoing unprotected sexual intercourse (without condom) with casual partners, are at risk of getting Chlamydia trachomatis infection. One of the significant, long term implications of risky sexual behaviours and sexually transmitted infection is infertility problems. The objectives of this study are to determine the seroprevalence of Chlamydia trachomatis (CT) among subfertile couples (husband and wife) of The Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN) Subfertility Clinic and the factors associated with it (i.e. socio-demographic, duration of marriage, infertility factor, knowledge, attitude, practice of risky sexual behaviour (RSB) and predictors of Chlamydia trachomatis infection). The study is a cross- sectional study involving 112 infertile couples who underwent fertility treatment at LPPKN Subfertility Clinic from February 2018 until February 2019. Socio-demographic factors, duration of marriage, infertility factor, knowledge, attitude and practice (KAP) of risky sexual behavior (RSB) variables were determined via self-administered questionnaire that includes close ended questions. Meanwhile, Chlamydia trachomatis antigen and antibody (CT IgG) were determined via Enzyme-Linked Immunosorbent Assay (ELISA) and rapid visual immunoassay test kit. This approach is selected to detect past and current infections of Chlamydia trachomatis through antibody and antigen detection in the blood serum, endocervical swab and urine samples. The response rate of this study was 97.39%. Majority of the respondents were aged between 25–34 years old and dominated by Malay ethnicity. Half of the respondents were among those with tertiary level of education and working in the private sector. In term of duration of marriage, half of the samples were couples who have been married for 3–7 years with majority of them had primary infertility. The female factor was reported to be the most dominant, followed by the unexplained factor and male factor. The seroprevalence of Chlamydia trachomatis among subfertile couples was 22.1% with 14.7% in husbands and 17.9%, was reported among wives. In terms of knowledge, the results showed that most couples had high level of knowledge about risky sexual behaviours with a score of more than the mean (> 6) for both husbands and wives. Meanwhile, each husband and wife group had positive attitude towards risky sexual behavior. Approximately, 35.7% of husbands and 12.5% of wives were engaged with risky sexual behavior while a higher percentage of premarital sex was reported among the husbands compared to the wives. The chi-square results showed no association between CT status and socio –demographic factors, marital status and knowledge of RSB among subfertile couples. A significant association was recorded between CT and practices of RSB among couples (p< 0.05) particularly among those with multiple sex partners and husbands who had premarital sex (p<0.05). However, the Binary Logistic Regression analysis showed that none of the selected variables were significant predictors of CT status among the couples (p> 0.05). This study has determined that the seroprevalence of Chlamydia trachomatis (22.1%) and practices of risky sexual behavior among subfertile couples were high. Even though the results have shown no association between the dependent and independent variables, our finding has given an evidence-based detection of past infection of Chlamydia trachomatis among subfertile couples. The practice of RSB has interrelated risk of getting CT and its long-term consequences particularly on women reproductive system. Since the awareness on CT among public is considered low, it is crucial to sensitize them about it to ensure early detection and prevention. Therefore, CT screening is strongly recommended to be integrated in fertility work up treatment and be promoted among sexually active adolescents and those young in age.